World Englishes in multilingual Morocco. Issue 2 (26th May 2020) - Soussi, Houssine
Abstract: This paper explores the history, politics and discourses around the situation of English(es) in Morocco. It examines how this global language succeeded to infiltrate into the Moroccan linguistic market with a focus on its various uses in various domains (education, academic research, diplomacy, mass media, tourism and finance). Albeit English(es) is spoken sporadically in the business, science and education sectors, its usage and learning have grown over the last decades with the boom of free English satellite channels and the development of the internet and social media. This language is now considered as the main vehicle for the transfer of technology and as an important tool of appropriating modernity. Indeed, it is gaining prestige among Moroccans and is quickly replacing French as Morocco's second language, both among youths and educators.